Smart Waste Collector - Tuan Ibrahim, Tuan Mohd Hafeez (Multidisciplinary Applied Research and Innovation, 2023)
Enough to feed 12 million people a day. That is how much Malaysians waste food every day. Solid Waste Management and Public Cleansing Corporation (SWCorp) deputy chief executive officer Mohammad Diah Wahari said Malaysians threw away 16,688 tonnes of food daily. Food waste in this country has reached a critical level as data by Solid Waste Management and Public Cleansing Corporation (SWCorp) shows that 55 percent of solid waste disposed at landfills comprises food. The reality, however, is that the food is still ending up in Malaysia’s landfills, and space is running out. Smart Waste Collector is a machine that functions to destroy food waste safely without the need to throw it directly into the trash can. This is because the continued disposal of food waste into the garbage will produce an unpleasant odor, especially for users who live in a hostile atmosphere that is large and does not have an effective waste disposal system. The leftovers will be crushed using rotating machine blades, and the crushed residue will collect at the bottom of the machine. In this study, the model of the Smart Waste Collector was fabricated to demonstrate the working principle to destroy the food waste into small pieces. Suggestion: Motor types and suitable current types need to be replaced to obtain higher power as to be able to decompose food waste into smaller lumps in larger quantities.